A Structural Retirement Model - Gustman, Alan L.; Steinmeier, Thomas L. (Econometrica, 1986)
The model analyzed here constrains most work on the main job to be full time. Partial retirement requires a job change and a wage reduction.Estimates of utility function parameters and their distributions incorporate information on age of leaving the main job and of full retirement. These estimates determine the slope at different ages and the convexity of within period indifference curves between compensation and leisure. Even though age specific dummy variables are not used, the model closely tracks retirement behavior. Policy analysis based on earlier models with simpler structures is shown to be misleading.